Invasive Fungal Infections after Natural Disasters - Kaitlin Benedict; Benjamin J. Park (Emerging Infectious Diseases, 2014)
The link between natural disasters and subsequent fungal infections in disaster-affected persons has been increasingly recognized. Fungal respiratory conditions associated with disasters include coccidioidomycosis, and fungi are among several organisms that can cause near-drowning pneumonia. Wound contamination with organic matter can lead to post-disaster skin and soft tissue fungal infections, notably mucormycosis. The role of climate change in the environmental growth, distribution, and dispersal mechanisms of pathogenic fungi is not fully understood; however, ongoing climate change could lead to increased disaster-associated fungal infections. Fungal infections are an often-overlooked clinical and public health issue, and increased awareness by health care providers, public health professionals, and community members regarding disaster-associated fungal infections is needed.